HISTORY, PRESENT AND DEVELOPMENT PROSPECTS OF THE WELL DRILLING DEPARTMENT OF THE IVANO-FRANKIVSK NATIONAL TECHNICAL UNIVERSITY OF OIL AND GAS - Martsynkiv, O.B.; Seniushkovych, M. V.; Kochkodan, Ya. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2023)
The history of the development of the Well Drilling Department is presented. The prerequisite for the establishment of the department was the resolution on the introduction of the basics of petroleum geology, drilling operations and chemical technology at Lviv Polytechnic School in 1882. In 1886, two-year preparatory courses in mining and metallurgy were launched at Lviv Polytechnic School. In 1893, the two-year courses were transformed into three-year courses with a focus on oil. In 1897, the Department of Mining was established at Lviv Polytechnic School. In the academic year 1917-1918, the Lviv Polytechnic School (now Lviv Polytechnic National Technical University) founded the Petroleum Department, and in 1922, the Department of Oil Drilling and Production was established. The article describes the periods of formation and development of the department: Lviv period from 1922 to 1941 at Lviv Polytechnic, and from 1944 to 1963 at Lviv Polytechnic Institute. The Ivano-Frankivsk period from 1963 to 1966 at the Ivano-Frankivsk branch of Lviv Polytechnic Institute, and from 1967 to the present day at the Ivano-Frankivsk Institute of Oil and Gas (now Ivano-Frankivsk National Technical University of Oil and Gas). The names of the professors who have headed the department for 100 years of its functioning are given. The structure of the Drilling Department as of today is described. The list of educational programs under which the department trains specialists of the first (bachelor's) level, second (master's) level and third (doctoral) level of higher education in the specialties 184-Mining and 185-Oil and Gas Engineering and Technology is provided. The list of the main disciplines taught by the Department of Drilling, as well as the published textbooks and manuals is provided. The list of research and training laboratories that operate at the department, their work on training students and advanced training of specialists in the specialty "Well Drilling", as well as conducting practical and laboratory trainings for specialists of drilling enterprises is given. The scientific schools functioning at the Department of Drilling are presented. The interrelation of the scientific work of the department with industry is described. The main tasks of the department are listed.